Autologous transplant vs oral chemotherapy and lenalidomide in newly diagnosed young myeloma patients: a pooled analysis - Gay, F; Oliva, S; Petrucci, M T; Montefusco, V; Conticello, C; Musto, P; Catalano, L; Evangelista, A; Spada, S; Campbell, P; Ria, R; Salvini, M; et al. (Leukemia, 2017)
In newly diagnosed myeloma patients, upfront autologous transplant (ASCT) prolongs progression-free survival 1 (PFS1) compared with chemotherapy plus lenalidomide (CC+R). Salvage ASCT at first relapse may still effectively rescue patients who did not receive upfront ASCT. To evaluate the long-term benefit of upfront ASCT vs CC+R and the impact of salvage ASCT in patients who received upfront CC+R, we conducted a pooled analysis of 2 phase III trials (RV-MM-209 and EMN-441). Primary endpoints were PFS1, progression-free survival 2 (PFS2), overall survival (OS). A total of 268 patients were randomized to 2 courses of melphalan 200 mg/m2 and ASCT (MEL200-ASCT) and 261 to CC+R. Median follow-up was 46 months. MEL200-ASCT significantly improved PFS1 (median: 42 vs 24 months, HR 0.53; P<0.001), PFS2 (4 years: 71 vs 54%, HR 0.53, P<0.001) and OS (4 years: 84 vs 70%, HR 0.51, P<0.001) compared with CC+R. The advantage was noticed in good and bad prognosis patients. Only 53% of patients relapsing from CC+R received ASCT at first relapse. Upfront ASCT significantly reduced the risk of death (HR 0.51; P=0.007) in comparison with salvage ASCT. In conclusion, these data confirm the role of upfront ASCT as the standard approach for all young myeloma patients.
Keywords: Stem Cell Transplantation; dospělí; záchranná terapie; thalidomid; Thalidomide; Adult; lenalidomid; lidé; autologní transplantace; transplantace kmenových buněk; mnohočetný myelom; Lenalidomide; Salvage Therapy; klinické zkoušky, fáze III jako téma; Aged; aplikace orální; Clinical Trials, Phase III as Topic; lidé středního věku; Multiple Myeloma; senioři; Administration, Oral; Transplantation, Autologous; Middle Aged; Humans